The Investigation of financial inclusions, financial literation, and financial technology in Indonesia - Muhammad Noor; Finnah Fourqoniah; Muhammad Fikry Aransyah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The Indonesian Financial Services Authority (Otoritas Jasa Keuangan) states that the financial literacy increase will be followed by developing the financial inclusion index. Nevertheless, the level of public financial literacy is still far behind the financial inclusion index. Perpres No. 82 of 2016 concerning the National Inclusive Finance Strategy sets a target of 75% of the adult population to access financial services in 2019. As information technology develops and internet penetration rates rapidly emerge, digital financial services emerge that make it easier for people to obtain financial services called financial technology. The increasing use of financial technology is one of the drivers for increasing national financial inclusion. This study aims to investigate studies of financial inclusion, financial literacy, both from knowledge, behavior, and financial attitudes, and financial technology. The research is a literature study research examining thirty journals and reports related to Financial Inclusion, Financial Literacy, and Financial Technology. Formed on the respondents' characteristics, gender, age, education, and occupation had an impact on increasing financial inclusion, financial literacy, and financial technology in Indonesia. Many people use financial products and services without having a good knowledge of the functions, how to choose the right according to needs, and do not know the risks of the products used. Recommendation from this is a strategy strategic of the respondents' characteristics is needed in increasing financial inclusion.